Modeling food price volatility and testing heat wave and/or meteor shower effects: Evidence for Asia and Pacific countries - Alom, Fardous; Bert , Ward; Baiding, Hu (Canadian Center of Science and Education, 2012)
This paper assesses the volatility and cross country mean and volatility spillover effects of food prices within and across global and selected Asian and Pacific countries namely Australia, New Zealand, South Korea, Singapore, Hong Kong, Taiwan, India and Thailand. The principal method of analysis comprises the development of a set of component GARCH-type models of conditional variance. Volatility characteristics and spillover effects of food prices are examined across a full (1995-2010) and two subsamples (1995-2001 and 2002-2010) with daily food price indices. Main findings of the study are as follows: (1) like other asset prices, food price volatility can be modelled by CGARCH variant of GARCH-family models for world as well as country specific levels, (2) increased risk does not necessarily lead to increased returns for world and specified countries except few instances, (3) mixed evidence of cross country mean and volatility spillover effects are reported. No exact direction of spillover effects from exporter to importer or importer to exporter countries can be drawn rather mixed evidence of spillover from exporter to importer, exporter to exporter, importer to exporter and geographical proximity can be documented. The ‘meteor shower’ hypothesis that the conditional variance of the change in one market depends on the past information of other markets dominates ‘heat wave’ hypothesis that the conditional variance depends on the past information of that market while for shorter time period ‘heat wave’ effects dominate ‘meteor shower’ effects